Generation Z's Understanding of Prenuptial Agreements from an Islamic Family Law Perspective: An Empirical Study in Gemawang Hamlet, Pakurejo, Indonesia - Ratna Ayunintyas; Sumarjoko; Eko Sariyekti (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study was motivated by Generation Z's limited understanding of marital rights and obligations, particularly regarding prenuptial agreements. Although digital media provides broad access to legal information, such access does not necessarily improve their understanding of Islamic family law. This study aims to examine Generation Z's understanding of prenuptial agreements from the perspective of Islamic family law. A qualitative field research approach was employed, with data collected through observation, in-depth interviews, and documentation involving married Generation Z participants in Gemawang Hamlet, Pakurejo Village, Temanggung Regency, Indonesia. The data were analyzed descriptively using Benjamin Bloom's theory of understanding and the perspective of Islamic family law. The findings indicate that participants' understanding of prenuptial agreements remains limited. Most viewed such agreements merely as instruments for the separation of marital assets, without adequately understanding their objectives, functions, and legal implications. The study also found that several participants entered marriage with insufficient knowledge of spouses' rights and obligations. From the perspective of Islamic family law, prenuptial agreements are permissible provided they do not contradict Sharia principles and serve to clarify the rights and obligations of both parties. Therefore, strengthening Islamic family law education is essential to improve Generation Z's preparedness for marriage.